Tax jurisdiction and E-Commerce - Paweł Szwajdler (Kazimierz Wielki University, 2017)
The aim of this work is to show main ideas related to tax jurisdiction with reference to e- commerce. The author is going to evaluate legal solutions, scientific ideas and proposals of international organizations, which concern subject of this paper.  In the beginning of the work, the author presents notions of direct and indirect e-commerce. The work also deals with tax jurisdiction in relation to income taxes and consumption taxes. The above-mentioned issues are discussed in relation to direct and indirect e-commerce. The author assesses positively regulations, which apply destination principle to consumption taxes. Furthermore, it is submitted that it is worth to consider entering into force regulations, which let find connection between persons and direct e -commerce enterprises so as to determine tax jurisdiction.